System modeling and optimization: 25th IFIP TC 7 Conference, CSMO 2011, Berlin, Germany, September 12-16, 2011, revised selected papers - Hömberg, Dietmar (Springer, 2013)
This book is a collection of thoroughly refereed papers presented at the 25th IFIP TC 7 Conference on System Modeling and Optimization, held in Dresden, Germany, in September 2011. The 55 revised papers were carefully selected from numerous submissions. They are organized in the following topical sections: control of distributed parameter systems; stochastic optimization and control; stabilization, feedback, and model predictive control; flow control; shape and structural optimization; and applications and control of lumped parameter systems
Keywords: Konferenzschrift -- 2011 -- Berlin; Systemmodell; Mathematisches Modell; Kontrolltheorie; Optimierung